2015
DOI: 10.1182/blood.v126.23.2603.2603
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK Inhibition Blocks Inflammatory Signaling in Acute Myeloid Leukemia

Abstract: Background: p38 mitogen-activated protein kinase (p38MAPK) is activated by various pro-inflammatory and stress-related stimuli, and has been an attractive therapeutic target for autoimmune diseases. p38MAPK (hereafter referred to as p38) signaling is also involved in cell proliferation, differentiation, apoptosis, and invasion, suggesting that it may be a potential therapeutic target for cancer. We found that inflammatory cytokines, including interleukin-1 (IL-1), promote growth and survival of more than half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Two frequently used inhibitors of p38 kinase signaling also closely mimicked the effect of p38 α kinase depletion on haematopoiesis, which confirmed that active kinase is required for the regular process. We suggest that, taken together, these findings could help us to understand the role of p38 α and its importance as a therapeutic target within some leukemic illnesses, as discussed recently [6770].…”
Section: Discussionsupporting
confidence: 56%
“…Two frequently used inhibitors of p38 kinase signaling also closely mimicked the effect of p38 α kinase depletion on haematopoiesis, which confirmed that active kinase is required for the regular process. We suggest that, taken together, these findings could help us to understand the role of p38 α and its importance as a therapeutic target within some leukemic illnesses, as discussed recently [6770].…”
Section: Discussionsupporting
confidence: 56%
“…A study showed that when HCK is targeted with small molecules, drug resistance is reduced [29]. Other protein kinases, such as SYK [33], BRAF, p38 (p38MAPK) [34], PDGFRα/β [35], FGFR1 [36], RET [37], FLT4 [38] and Tie2 [39] have also been linked to leukemia. All these data further strengthen the consensus in the field that leukemia is a heterogeneous disease and hence targeting the aforementioned multiple kinase pathways could lead to a better outcome [40].…”
Section: Resultsmentioning
confidence: 99%
“…Immunosuppressive drugs such as antithymocyte globulin (ATG), cyclosporine (CS), and mycophenolate mofetil (MM) have been studied in low risk MDS [ 33 ], but still underutilized in MDS patients due to conflicting data and variable rates of response reported by the different studies [ 34 – 36 ]. Also, MAPK and TLR inhibitors, which target overactive TLR pathways in MDS, are currently being evaluated in several clinical trials [ 8 , 37 , 38 ]. Checkpoint inhibitors are another family of drugs that have been approved for solid tumors and now being investigated in high risk MDS and other hematologic malignancies such as AML [ 1 ].…”
Section: Immune Mechanisms In Mdsmentioning
confidence: 99%